HYBRID INNOVATION IN MEIJI, JAPAN*. (17th April 2013) - Nicholas, Tom
<x xml:space="preserve">Abstract</x> Japan's hybrid innovation system during the Meiji era provides a useful laboratory for examining the effectiveness of complementary incentives to patents. Patents were introduced in 1885, and by 1911 1.2 million mostly nonpecuniary prizes were awarded at 8, 503 competitions. Prizes provided a strong boost to patents, especially in less developed prefectures, and they also induced large spillovers of technical knowledge in prefectures adjacent to those with prizes, relative to distant control prefectures without prizes. Linking competition expenditures with the expected market value of patents induced by the prizes permits a cost–benefit assessment of the prize competitions to be made.